INTERNATIONAL BEST PRACTICES IN HOMEWORK ASSIGNMENT AND THEIR APPLICABILITY IN EDUCATION - Boltaboyeva Dilfuza Bozorboy qizi (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract Homework is an essential component of the educational process that reinforces classroom  learning,  develops  independent  study  habits,  and  enhances  academic achievement. Different countries have adopted diverse homework policies to maximize student engagement and learning outcomes while minimizing stress and burnout. This article examines international best practices in homework assignment from Finland, Japan, Singapore, Germany, Canada, South Korea, and the United States. The study analyzes the key features of these approaches and discusses their applicability in local educational  contexts.  Findings  suggest  that  effective  homework  should  emphasize quality over quantity, promote self-directed learning, integrate technology, encourage parental  involvement,  and  provide  differentiated  learning  opportunities.  Adapting these practices can contribute to improved student motivation, academic performance, and overall well-being.